Helicobacter pylori infection is associated with favorable outcome in advanced gastric cancer patients treated with S‐1 adjuvant chemotherapy. Issue 5 (22nd January 2018) - Nishizuka, Satoshi S.; Tamura, Gen; Nakatochi, Masahiro; Fukushima, Norimasa; Ohmori, Yukimi; Sumida, Chihiro; Iwaya, Takeshi; Takahashi, Takashi; Koeda, Keisuke; ,
Abstract : Background and Objectives: Limited information exists regarding beneficial effects of Helicobacter pylori . To examine the effect in advanced gastric cancer, we compared survival for patients treated with surgery‐only or adjuvant chemotherapy on the basis of H. pylori infection status. Methods: A cohort of 491 patients who underwent R0 resection for locally advanced gastric cancer between 2000 and 2009 at 12 institutions in northern Japan was included. H. pylori infection status, was assessed from paraffin‐embedded formalin‐fixed samples. Overall survival (OS) and disease‐free survival (DFS) in surgery‐only (Surgery) and adjuvant chemotherapy (S‐1) groups were analyzed. A propensity score matching was employed to correct for confounding factors by indication. Results: H. pylori infection was positive in 175 patients and negative in 316 patients. H. pylori ‐positive patients showed significantly better survival than H. pylori ‐negative patients in both OS (hazard ratio [HR] 0.593, 95% confidence interval [CI] 0.417‐0.843; P = 0.003]) and DFS (HR 0.679, 95%CI 0.492‐0.937; P = 0.018). Propensity score matching further confirmed that S‐1 was virtually only effective when tumors were H. pylori ‐positive. Conclusions: The favorable outcome of H. pylori ‐positive patients implies that the host immune system is modulated by H. pylori enhancing the chemotherapeutic efficacy.